A Modified Mercalli Intensity map of Bangladesh: a proposal for zoning of earthquake hazard - Alam, Edris (Frontiers in Earth Science, 2023)
Bangladesh is vulnerable to a variety of natural hazards including frequent tropical cyclones, floods and, less commonly, earthquakes and tsunamis. The country has developed an effective response mechanism for frequently experiencing hazards. However, at the same time, the nation has not developed an effective response mechanism for earthquake as a result of limited experiences with this type of hazard in the recent past. This research constructs a new catalogue consisting of 144 earthquakes (between 810BC and 2015) occurring within Bangladesh and the adjacent region. From this new catalogue, the effects of earthquakes are available for 80 events which are used in order to construct the geography of hazard in Bangladesh. The construction of a detailed Modified Mercalli Intensity (MMI) map using the new earthquake data suggests that this will be useful for supporting future risk reduction efforts in Bangladesh. Specifically, the findings support the revision of the current seismic zoning map of Bangladesh to include Chittagong and Dhaka in the high-risk zone for effective earthquake risk reduction. Finally, this research concludes that analyses of long-term data helps to identify new hazard exposure and develop knowledge that is useful to formulate new disaster risk reduction policies and rectify existing know zones in Bangladesh.